Circuits of faith : migration, education, and the Wahhabi mission - Farquhar, Michael (Michael J.) (Stanford studies in Middle Eastern and Islamic societies and cultures., 2017)
The Islamic University of Medina was established by the Saudi state in 1961 to provide religious instruction primarily to foreign students. Students would come to Medina for religious education and were then expected to act as missionaries, promoting an understanding of Islam in line with the core tenets of Wahhabism. By the early 2000s, more than 11,000 young men from across the globe had graduated from the Islamic University. 'Circuits of Faith' offers the first examination of the Islamic University and considers the efforts undertaken by Saudi actors and institutions to exert religious influence far beyond the kingdom's borders.